Удмуртские фольклорные танцы - Батурина Е. Н. (Удмуртский государственный университет, 2002)
Экземпляры: ЦБ (20241209) / Инвентарный номер: 35265 / Цена: 40.00 / Сис.шифр: 85.32(2Рос.Удм) / Авт.знак: Б 28 / ГРНТИ: 18 / ББК: 85.32(2Рос.Удм)